Economics Of Meat Production Of Desi Duicks - George OJ (Department of Poultry Science, College of Veterinary and Animal Sciences, 1978)
An experiment was designed to evaluate the meat production potentialities of straight run Desi ducklings. 110 desi one-day-old ducklings divided in to two equal groups which formed the replicates. Identical feed and managemental practices were employed in the trial. After an initial brooding of 3 weeks in a battery brooder, they were reared on floor upto ten weeks of age.